Building an international precision medicine platform trial for the acute respiratory distress syndrome (ARDS): an expert consensus project report - Kiran Reddy; Neil Aggarwal; Narges Alipanah-Lechner; Djillali Annane; David B Antcliffe; Daphne Babalis; J Kenneth Baillie; Abigail Beane; Lieuwe DJ Bos; Aidan Burrell; Carolyn S Calfee; Kiki Cano-Gamez; et al. (Efficacy and Mechanism Evaluation)
Background Almost all large-scale trials of disease-modifying therapeutic agents in critical care have failed to show benefit for patients, which may be explained in part by the clinical and biological heterogeneity inherent in virtually all critical illness syndromes. Enrichment strategies have been developed to separate responders from non-responders and better target treatments. In patients with the acute respiratory distress syndrome, a critical illness syndrome involving severe lung inflammation, latent class analysis and other clustering approaches have led to the discovery of subgroups (phenotypes) that appear to respond differently to treatment based on retrospective analyses of published clinical trials and observational cohorts. The next step is to test these phenotypes in a prospective trial. Rapid, point-of-care analytical methods have now made such a trial possible. There is a need to advance treatment for patients with acute respiratory distress syndrome and other critical illness syndromes by incorporating a phenotype-based approach into prospective trial design. The hyperinflammatory and hypoinflammatory phenotypes, that have been identified in acute respiratory distress syndrome, will be the first to be included in such a trial, with scope for further phenotypes to be studied over time. Future work This Efficacy and Mechanism Evaluation report, through expert consensus, describes a new Phase II, multiarm, adaptive platform randomised controlled trial design that tests multiple pharmacological therapies in a population of patients with acute respiratory distress syndrome stratified by baseline inflammatory phenotype. This report also reviews issues to be considered in developing precision medicine trials in critical care, which are designed with newly developed clinical phenotypes in mind. This work has been used to develop the Precision medicine Adaptive Network platform Trial in Hypoxaemic acutE respiratory failuRe precision medicine trial in acute respiratory distress syndrome, which has been funded and will begin recruitment in June 2025. Limitations This report is the result of expert consensus review, rather than utilising strict review methodologies (e.g. Delphi consensus process). However, expert consensus has been found to generate similar results to consensus processes when a high degree of agreement is reached and > 70% agreement was reached for all included recommendations. Funding This article presents independent research funded by the (NIHR) Efficacy and Mechanism Evaluation programme as award number NIHR154493. Plain language summary Almost all attempts to find new medicines that can help patients in intensive care have not worked. One explanation could be that groups of intensive care patients whom we think are similar are actually different from each other in their underlying biology. A treatment that we use in a clinical trial might work for some patients with a critical illness syndrome but may not work for others with the same syndrome, or worse, cause harm. We need better ways to identify groups of patients for whom a new treatment will work. This is a problem for patients with the acute respiratory distress syndrome, which is a syndrome of lung failure and inflammation in intensive care. Many patients with acute respiratory distress syndrome do not survive, and many of those who do survive have prolonged health problems and disability. Based on information from previous clinical trials, researchers have discovered the ‘hyperinflammatory’ and ‘hypoinflammatory’ subgroups (phenotypes) of acute respiratory distress syndrome, which may respond differently to new treatments. New advances have made it possible to quickly determine whether an individual patient has the hyperinflammatory or hypoinflammatory phenotype. This means that we can design large clinical trials to determine whether new medicines work better for one subgroup than the other. This Efficacy and Mechanism Evaluation report reviews new designs for clinical trials based on recent learnings from the coronavirus disease discovered in 2019 pandemic, new approaches to defining intensive care syndromes and new research about the biology of acute respiratory distress syndrome. This report describes a new clinical trial designed by a group of international researchers that will determine whether some medicines work differently for acute respiratory distress syndrome patients with the hyperinflammatory or the hypoinflammatory phenotypes, and it provides the blueprints for how the clinical trial might be adapted to test medicines in other phenotypes as we learn more. This new approach will be important for developing individualised, ‘precision medicine’ for patients in intensive care units.